2013
DOI: 10.21098/bemp.v15i4.432
|View full text |Cite
|
Sign up to set email alerts
|

The Islamic Capital Market Volatility: A Comparative Study Between in Indonesia and Malaysia

Abstract: This study attempts to examine the short-term and long-term relationship among selected global and domestic macroeconomic variables from each country (Fed rate, crude oil price, Dow Jones Index, interest rate, exchange rate and inflation) for Indonesia and Malaysia Islamic capital market (Jakarta Islamic Index (JII) and FTSE Bursa Malaysia Hijrah Shariah Index (FHSI). The methodology used in this study is vector error correction model (VECM) for the monthly data starting from January 2006 to December 2010. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
1
10
0
1
Order By: Relevance
“…In the context of Indonesia, both short-and long-run relationship between macroeconomic determinants and Islamic stocks using Vector Error Correction Model (VECM) (Antonio et al, 2013) and variance decompositions (Majid, 2016) techniques, found that inflation, money supply, exchange rate, and crude oil price significantly affected the Islamic stocks, showing the importance of these macroeconomic determinants to be focused on when stabilizing Islamic stock markets in the country. As for measuring the volatilities of Islamic stock markets, in his simple study using only the Time Series Plots and Histogram, Tanjung (2014) found that the Jakarta Islamic Index (JII) was abnormally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Indonesia, both short-and long-run relationship between macroeconomic determinants and Islamic stocks using Vector Error Correction Model (VECM) (Antonio et al, 2013) and variance decompositions (Majid, 2016) techniques, found that inflation, money supply, exchange rate, and crude oil price significantly affected the Islamic stocks, showing the importance of these macroeconomic determinants to be focused on when stabilizing Islamic stock markets in the country. As for measuring the volatilities of Islamic stock markets, in his simple study using only the Time Series Plots and Histogram, Tanjung (2014) found that the Jakarta Islamic Index (JII) was abnormally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, this is an opportunity for companies to boost the amount of exports that can in turn affect corporate earnings and encourage rising stock prices. From different studies there are differences in the findings, Sakti & Harun (2013); Bekhet & Matar (2013); and Antonio et al, (2013) that the exchange rate has a positive relationship with the stock price index. In contrast to the findings of Oktarina, (2017); Artini et al, (2017); and Wei et al, (2019) exchange rates have a negative effect on stock prices.…”
Section: Exchange Ratementioning
confidence: 87%
“…The focus in this study is on equities, so when investing in the capital market the value of stock prices becomes an important consideration. According to Antonio et al, (2013) the price of shares on the capital market is not only influenced by internal companies, but can also be influenced by macroeconomic variables. Stable macroeconomic conditions ensure that investors feel safe and comfortable investing their funds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries with good economic stability usually have stable currencies and their movements. Countries with poor economic stability, their currencies tend to move erratically and tend to weaken [14,15].…”
Section: B Effects Of Exchange Rates On the Indonesian Sharia Stockmentioning
confidence: 99%